Measles-related hospitalizations and associated complications in Jerusalem, 2018–2019. (May 2020) - Ben-Chetrit, E.; Oster, Y.; Jarjou'i, A.; Megged, O.; Lachish, T.; Cohen, M.J.; Stein-Zamir, C.; Ivgi, H.; Rivkin, M.; Milgrom, Y.; Averbuch, D.; Korem, M.; et al.
ABSTRACT: Objectives: The 2018 measles outbreak in Israel affected >2000 people in Jerusalem. The aim of the study was to describe clinical features and complications of hospitalized measles patients in Jerusalem, as related to age group and risk factors. Methods: All individuals hospitalized with measles in the three main hospitals in Jerusalem during March 2018 to February 2019 were included. Demographic, clinical and laboratory data were analysed. Results: Of 161 hospitalized individuals, 86 (53.4%) were <5 years old, 16 (10%) were ≥5 years but <20 years old, and 59 (36.6%) were ≥20 years old. Most, 114/135 (85%), were unvaccinated. Immunocompromised state was identified in 12/161 (7.5%) patients, 20/161 (12.4%) had other underlying co-morbidities, and four were pregnant. Hypoxaemia on admission was a common finding in all age groups. Hepatitis was more common among adults ≥20 years old (33/59, 59%). Measles-related complications were noted in 95/161 (59%) patients, and included pneumonia/pneumonitis (67/161, 41.6%), which was more common in young (<5 years) children, diarrhoea (18/161, 11.2%), otitis (18/161, 11.2%), and neurological complications (6/161, 3.7%)—the latter occurring more frequently in the 5- to 20-year age group. Two of the 12 immunocompromised patients died of measles-related complications. A high re-admission rate (19/161, 11.8%) within 3 months was documented among hospitalized measles patients. Conclusion: The burden of hospitalization, as well as the high rate of short- and long-term complications observed in hospitalized patients, underscore the importance of maintaining a high measles vaccine coverage, with enhanced targeting of unvaccinated population pockets.